Nasal immunization with H7 flagellin protects mice against hemolytic uremic syndrome secondary to Escherichia coli O157:H7 gastrointestinal infection - Bernal, Alan Mauro; Sosa, Fernando Nicolás; Todero, María Florencia; Montagna, Daniela Romina; Vermeulen, Mónica Elba; Fernández-Brando, Romina Jimena; Ramos, María Victoria; Errea, Agustina Juliana; Rumbo, Martin; Palermo, Marina Sandra (Frontiers in Cellular and Infection Microbiology, 2023)
Shiga-toxin (Stx) producing Escherichia coli (STEC) O157:H7 is the most frequent serotype associated with hemolytic uremic syndrome (HUS) after gastrointestinal infections. Protection against HUS secondary to STEC infections has been experimentally assayed through the generation of different vaccine formulations. With focus on patients, the strategies have been mainly oriented to inhibit production of Stx or its neutralization. However, few approaches have been intended to block gastrointestinal phase of this disease, which is considered the first step in the pathogenic cascade of HUS. The aim of this work was to assay H7 flagellin as a mucosal vaccine candidate to prevent the systemic complications secondary to E. coli O157:H7 infections. The cellular and humoral immune response after H7 nasal immunization in mice were studied by the analysis of systemic and intestinal specific antibody production, as well as cytokine production and lymphocyte proliferation against H7 flagellin ex vivo. Immunized mice developed a strong and specific anti-H7 IgG and IgA response, at systemic and mucosal level, as well as a cellular Th1/Th2/Th17 response. H7 induced activation of bone marrow derived dendritic cells in vitro and a significant delayed-type hypersensitivity (DTH) response in immunized mice. Most relevant, immunized mice were completely protected against the challenge with an E. coli O157:H7 virulent strain in vivo, and surviving mice presented high titres of anti-H7 and Stx antibodies. These results suggest that immunization avoids HUS outcome and allows to elicit a specific immune response against other virulence factors.